Episodic autobiographic retrieval: Memories dissolving with time? - Vranić, Andrea (2010)
Cross-sectional studies show a linear decrease in memory performance as a function of age for episodic (autobiographic) memory (ABM). The hallmark of episodic retrieval is the mental travel back in time to the original episode and „re-living“ of the remembered event. This subjective mental time travel is mediated by a special type of awareness called autonoetic consciousness. Typical content-based approach to assessment of ABM rarely takes this subjective mental experience into consideration, focusing solely on the „what-where-and-when“ of the event. In this study we addressed the issue of the decreasing ABM found in elderly. More specifically, we probed for changes in the behavioral indices of autonoetic consciousness and the details of autobiographical events recalled for memories with retention intervals ranging across the lifespan. A sample of N=50 elderly individuals (age range 60-70) were asked to recall 3 personal events during a semi-structured interview. These events were specified in terms of life-period (childhood, early, middle or late adulthood, and recent events) and the degree of social interaction and/or emotional tone (e.g. social occasion or medical appointment). The order of specified events was counterbalanced. Memory for each event was rated using the Memory Characteristic Questionnaire (MCQ). Following the MCQ, the description of each event was given and rated using the autonoetic subscale of the Episodic Autobiographical Memory Interview (EAMI). The results show a linear decrease in detail specificity and reliving judgments as a function of memory remoteness, mirroring the age-related decrease in ABM performance.
Projekt MZOS
ENG